Diffuse large B-cell lymphoma causing acute liver failure: a rare case of survival. (12th May 2015) - Kapuria, Devika; Strasser, Kristen; Qasem, Abdulraheem
Abstract : Acute liver failure is a rare but life-threatening illness with an incidence of 2–8 per million population. The most common causes of acute liver failure include drug ingestion and viral hepatitis followed by ischaemic hepatocellular injury and, less commonly, malignancy. Our patient presented with acute liver failure, which was found to be secondary to hepatic infiltration by diffuse large B-cell lymphoma. He received early treatment and has been in remission for more than a year after his initial presentation. To the best of our knowledge, our patient is the second reported survivor of acute liver failure caused by malignant hepatic infiltration by diffuse large B-cell lymphoma.